2021
DOI: 10.1186/s12864-021-07710-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome resequencing provides insights into the population structure and domestication signatures of ducks in eastern China

Abstract: Background Duck is an ancient domesticated animal with high economic value, used for its meat, eggs, and feathers. However, the origin of indigenous Chinese ducks remains elusive. To address this question, we performed whole-genome resequencing to first explore the genetic relationship among variants of these domestic ducks with their potential wild ancestors in eastern China, as well as understand how the their genomes were shaped by different natural and artificial selective pressures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…However, high TYRP1 activity leads to the production of eumelanin, while low TYRP1 activity leads to the production of pheomelanin [ 16 ]. Furthermore, a study demonstrated that the mutation of the chicken TYRP1 gene significantly affected the skin color, tibia color, and claw color of silk-feathered black chickens, and the expression of the TYRP1 gene was consistent with the deposition and distribution of melanin [ 17 ]. In contrast, Gratten et al found that there was no significant difference in TYRP1 gene expression between dark and light-colored Soai sheep [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, high TYRP1 activity leads to the production of eumelanin, while low TYRP1 activity leads to the production of pheomelanin [ 16 ]. Furthermore, a study demonstrated that the mutation of the chicken TYRP1 gene significantly affected the skin color, tibia color, and claw color of silk-feathered black chickens, and the expression of the TYRP1 gene was consistent with the deposition and distribution of melanin [ 17 ]. In contrast, Gratten et al found that there was no significant difference in TYRP1 gene expression between dark and light-colored Soai sheep [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also noted that GS/65 did not cause any mortality in infected ducks, yet it spread systemically in infected birds. Additionally, while Shaoxin ducks and Pekin ducks did originate from the same lineage, they have been selectively bred for eggs or meat (respectively) and inhabit separate clades in phylogenetic analyses (72,73). It is also likely that this selective breeding has resulted in differences in immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Waterfowl resources are rich in China, and the Genetic Resources Committee has officially recognized these resources [ 1 , 2 ]. There are many possible origins of indigenous duck breeds in China [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%